2015
DOI: 10.1038/srep09077
|View full text |Cite
|
Sign up to set email alerts
|

Higher order microfibre modes for dielectric particle trapping and propulsion

Abstract: Optical manipulation in the vicinity of optical micro- and nanofibres has shown potential across several fields in recent years, including microparticle control, and cold atom probing and trapping. To date, most work has focussed on the propagation of the fundamental mode through the fibre. However, along the maximum mode intensity axis, higher order modes have a longer evanescent field extension and larger field amplitude at the fibre waist compared to the fundamental mode, opening up new possibilities for op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 46 publications
2
49
1
Order By: Relevance
“…Besides providing the effective sensing volume of a single ONF for a given particle size, the separation-transmission dependence could be useful for profiling electromagnetic fields that have complex profiles, e.g., for higher order modes propagating in an ONF [27,34]. We also show that the observed, unexpected transmission dependence at small separations cannot be directly explained by the simplistic model we employed, which relies on the field overlap integral, and this clearly requires further investigation.…”
Section: Fiber Transmission As a Function Of Fiber-particle Separationmentioning
confidence: 73%
See 2 more Smart Citations
“…Besides providing the effective sensing volume of a single ONF for a given particle size, the separation-transmission dependence could be useful for profiling electromagnetic fields that have complex profiles, e.g., for higher order modes propagating in an ONF [27,34]. We also show that the observed, unexpected transmission dependence at small separations cannot be directly explained by the simplistic model we employed, which relies on the field overlap integral, and this clearly requires further investigation.…”
Section: Fiber Transmission As a Function Of Fiber-particle Separationmentioning
confidence: 73%
“…The evanescent field structures of non-uniform fiber elements [36] and complex evanescent fields under counter propagating light [22] and higher mode propagation [27,34,37] may also be investigated using this system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent proposals have shown that higher order fiber modes (HOMs) can be used to trap atoms [5], making the use of HOMs in MNFs of interest. Due to the improvements in higher order mode MNF fabrication methods [6], some initial experimental studies on (i) the interactions between atoms and HOMs [7] and (ii) the interaction between microparticles and HOMs [8] have been reported. These works exploit the important advantages of HOMs, such as longer evanescent field extension, three dimensional field arrangements and larger mode cut off diameter of the fiber compared to that which can be obtained using the fundamental mode.…”
Section: Introductionmentioning
confidence: 99%
“…When a process of mode-conversion happens the differential change in momentum is compensated by a momentum transfer to the nearby atom. Based on this effect, recent papers have explored the possibility of using higher-order modes to control center-of-mass motion of trapped atoms Ebongue et al (2016) and trapped microparticles Maimaiti et al (2015) along the nanofiber.…”
Section: Trapping With Higher-order Modesmentioning
confidence: 99%